Motor-enriched learning for improving pre-reading and word recognition skills in preschool children aged 5–6 years – study protocol for the PLAYMORE randomized controlled trial - Gejl, Anne Kær (BMC Pediatr, 2021)
BACKGROUND: Results from previous studies suggest that bodily movements, spanning from gestures to whole-body movements, integrated into academic lessons may benefit academic learning. However, only few studies have investigated the effects of movement integrated into reading practice. The PLAYMORE study aims to investigate the effects of two interventions focusing on a close and meaningful coupling between bodily movement and academic content on early pre-reading and word recognition skills in children. Further, the study aims to compare two interventions involving either hand movements (i.e. using arms and hands) or whole-body movements (i.e. using the whole body). Potential mediating factors underlying the link between bodily movement on early pre-reading and word recognition skills will be explored. METHODS/DESIGN: The PLAYMORE study will be conducted as a three-armed randomized controlled trial including children aged five to six years recruited from four schools in the Copenhagen area, Denmark. Stratified by class, children will be randomly allocated to one of three 8-week intervention/control periods: 1) teaching involving whole-body movements, 2) teaching involving hand movements (i.e. arms and hands) or 3) teaching involving minimal motor movements (i.e. seated on a chair using paper and pencil). Outcome measurements, including pre-reading and word recognition skills, will be collected before and after the intervention period to assess the intervention effects. This study protocol follows the SPIRIT guidelines. DISCUSSION: The PLAYMORE study will add to the current knowledge concerning the link between bodily movement and academic performance with important details about pre-reading and word recognition skills in preschool children. If effective, evaluation of the implementation of the PLAYMORE program should be conducted in order to investigate whether the effects can be transferred into standard school settings. The PLAYMORE study will lay the foundation for future research that have the potential to inform the political and scientific debate and importantly, to provide teachers with detailed information of how to implement movements effectively during teaching in order to support and motivate children in the process of learning to read. TRIAL REGISTRATION: The study was retrospectively registered in ClinicalTrials.gov (NCT04618822) the 5th of November 2020.